Enhancing soft soil strength by using jute fibre and human hair fibre as reinforcing materials - Mohamad Shakri Mohmad Shariff; Mohamed Ahmed Hafez; Nazaruddin Abdul Taha; Nor Faiza Abdul Rahman; Munira Mohammad (Semarak Ilmu Publishing, 2025)
Clayey soil often displays unfavourable soil properties, rendering it unsuitable for construction endeavours due to its low load-bearing capacity and high compressibility, particularly when utilised as a subgrade layer. Hence, it is crucial to do soil stabilisation before commencing construction works, and typical stabilising materials, including fly ash, coir fibre, cement, and lime, are commonly utilised, which may involve cost and environmental impact since fly ash is known as a hazardous material to human health. The objective of this study is to examine the application of jute fibre in conjunction with human hair fibre as a stabiliser to improve the characteristics of clay soil, hence enhancing the unconfined compressive strength (UCS). Various experiment tests are conducted, including sieve analysis tests, Atterberg limit tests, and standard proctor tests. These tests are conducted to confirm that the soil sample collected from the west coast of Malaysia is soft clay soil and suitable for this study. The unconfined compressive test is performed to examine the effect of using jute fibre and human hair fibre on increasing the UCS of soft soil. Various soil specimens were prepared, including a controlled sample and various combinations of jute fibre (0.4%, 0.8%, 1.2%, 2%, and 2.5%) with human hair fibre (0.5%, 1%, 1.5%, 2%, and 2.5%). Utilising jute fibre and human hair fibre as stabilisers for soft clay soil resulted in a significant increase in shear strength. The use of 1.2% jute fibre combined with 1.5% human hair fibre led to an enhancement in compressive strength from 1209.101 kN/m2 to 1465.896 kN/m2 following a curing period of 7 and 14 days. In conclusion, it has been demonstrated that incorporating jute fibre and human hair fibre into the soft soil enhances soil strength performance. Nevertheless, exceeding the quantity of fibres mixed into the soil results in the opposite effect. Optimal soil stabilisation occurs when the jute fibre content is 1.2% combined with 1.5% of human hair fibre.